Pengaruh Pola Kontrol Terhadap Tingkat Perilaku Sosial Peserta Didik di Sekolah - Supriadi Torro (Rayhan Intermedia, 2022)
This study aims to determine the effect of control patterns on the level of social behavior of students. The type of research used is quantitative research. The population in this study were students of class X and XI SMA Negeri 4 Makassar, as many as 703 people with a total sample of 87 people who were selected through random sampling. Data collection techniques were carried out by means of questionnaires and documentation. Data analysis techniques are descriptive statistical analysis, and inferential statistical analysis. The results showed that: 1) There was an effect of preventive control patterns (X1) on the level of social behavior of students (Y) of 0.393 or 39.3%. 2) There is an effect of repressive control patterns (X2) on the level of social behavior of students (Y) of 0.381 or 38.1%. 3) There is an effect of the pattern of curative control (X3) on the level of social behavior of students (Y) of 0.175 or 17.5%. 4) While the results of the hypothesis simultaneously or together (X1, X2 and X3) affect the level of social behavior of students (Y) by 0.613 or 61.3% and the rest is influenced by other variables.